2003
DOI: 10.1055/s-2003-40270
|View full text |Cite
|
Sign up to set email alerts
|

Hemiatrophia faciei progressiva und Pupillotonie

Abstract: We assume that in our case the pupillotonia as well as the hemiatrophia faciei and the epilepsy is caused by a common autoimmune factor. All other aetiologies for these three diseases were excluded. Furthermore, the occurrence of pupillotonia, hemiatrophia faciei and epilepsy was simultaneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Aynaci et al [ 16 ] described a child with hemifacial atrophy features without any neurological deficiency, with Adie's syndrome on the affected side of the face—with mydriasis, no reaction to light, and with a slow reaction to convergence and accommodation (tonic pupil). Schnitzler et al [ 17 ] have reported a 25-year-old patient who at the age of 14 had a tonic pupil on the right side and epilepsy attacks. Both these patients had Adie's syndrome in which Adie's tonic pupil is a part of the immunological etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Aynaci et al [ 16 ] described a child with hemifacial atrophy features without any neurological deficiency, with Adie's syndrome on the affected side of the face—with mydriasis, no reaction to light, and with a slow reaction to convergence and accommodation (tonic pupil). Schnitzler et al [ 17 ] have reported a 25-year-old patient who at the age of 14 had a tonic pupil on the right side and epilepsy attacks. Both these patients had Adie's syndrome in which Adie's tonic pupil is a part of the immunological etiology.…”
Section: Discussionmentioning
confidence: 99%